Impact of learning orientation on innovation in Colombian SMEs - Contreras Palacios, Fred D.; Gálvez Albarracín, Edgar J.; González-Campo, Carlos H. (Cuadernos de Administración, 2012)
Multiple studies worldwide show that innovation is a source of competitive advantage and it is, therefore, important to know the factors that stimulate it. That is why the research presented here seeks to analyze the effect of organizational learning orientation on business innovation. This empirical study was conducted with 403 Colombian SMEs. The results obtained through multiple linear regression showed a highly positive effect on the relationship studied, which has important implications for employers, academia, and government, as told to a management style that encourages such practices in the organization divergence, the generation of new ideas, risk taking, knowledge sharing, cooperation agreements with universities and other companies, openness, experimentation and continuous change generate better innovation performance.